Odpowiedź:
p)
2 1/3 + 3/4 : 1/2 = 2 1/3 + 3/4 * 2 = 2 1/3 + 3/2 = 2 1/3 + 1 1/2 = 2 2/6 + 1 3/6 =
= 3 5/6
g)
(2 11/12 : 2 1/3) : (2 1/3 : 1/16) = (35/12 : 7/3) : (7/3 * 16) = (35/12 * 3/7) : 112/3 =
= 5/4 * 3/112 = 15/448
r)
1/4 + 1/12 + 6/8 - 1/12 = 2/8 + 6/8 = 8/8 = 1
s)
3/9 - 2/3 + 6/18 + 4/6 = 1/3 - 2/3 + 1/3 + 2/3 = 2/3
t)
3/4 + 2 1/10 - 2/8 = 6/8 - 2/8 + 2 1/10 = 4/8 + 2 1/10 = 1/2 + 2 1/10 =
= 5/10 + 2 1/10 = 2 6/10 = 2 3/5
u)
8/12 - 1/3 + 3 2/6 = 2/3 - 1/3 + 3 1/3 = 2/3 + 3 = 3 2/3
w)
1/5 - 1/4 - 3/15 + 1/8 = 1/5 - 1/5 - 2/8 + 1/8 = -1/8
Szczegółowe wyjaśnienie: